: (Studi pada Fakultas Ilmu Sosial Dan Politik Universitas Islam Balitar) - Basuki, Hery (Translitera : Jurnal Kajian Komunikasi dan Studi Media, 2022)
The performance attitude of employees also depends on the way the leader performs. Reliable human resources become a reference for achieving common goals. The researcher aims to see whether leadership style has an influence on employee performance at the Faculty of Social and Political Sciences, Unisba Blitar. The study was carried out with a total sample of 35 people. Data analysis through instruments, then test normality and heterochemisticity. The hypothesis test is carried out with the T test. The results showed that the significance value was 0.008 < 0.05 from the hypothesis test partially so that it could be interpreted that Ha was accepted and Ho was rejected, therefore the leadership style had an effect on employee performance at Fisip Unisba Blitar.